Evaluating the national academic reference standards (NARS) engagement into academic programs under accreditation standard to better insure higher quality education in Syria (Case study for business management Program _ Faculty of Economy in Tishreen Univ - طرابلسية شيراز (Latakia University Journal - Economic and Legal Sciences Series, 2024)
This research aims to study the extent of the impact of website design for Syrian government universities (method of use, content, interactivity, attractiveness, service value) on evaluating the quality of educational services provided (reliability, responsiveness, security and reliability). To achieve this goal, a case study was conducted that included the Tishreen University website. The current study relied on the descriptive analytical approach. An electronic questionnaire was designed for the purpose of collecting primary data and was distributed to a purposive sample that included (300) male and female students from various colleges who had previously used the Tishreen University website. The collected data were then analyzed and hypotheses tested using SPSS.25. The study reached a set of results, the most important of which are: the existence of a statistically significant relationship between the design dimensions of the Tishreen University website and the quality of educational services provided by this website; There was a significant positive impact of using the university’s website on the security and reliability of the educational services it provides, and the interactivity of the website had a striking impact on the response of the students who used it, while the content of the website was the design criteria that had the least impact on the quality of the educational services provided, through its weak effect in the reliability of those services. This study had a set of recommendations, including the need for Syrian government universities to keep up with modern developments in website design, as well as the importance for the administrators of Tishreen University website to focus on designing the university’s website and enhancing the quality of educational services it provides.